Patient concerns regarding antidepressant drug-drug interactions: a retrospective analysis using data from a medicines call centre - Treasure M. McGuire; Geraldine M. Moses; David M. Pache; Mieke L. van Driel; Samantha A. Hollingworth; Hyang Joo Lim; Edgar L. Poon (CSIRO Publishing, 2022)
Introduction Antidepressant use has increased over the last two decades, with Australia and New Zealand among the highest antidepressant users in Organisation for Economic Co-operation and Development (OECD) countries. Comorbidity and polypharmacy are common in antidepressant users, increasing the likelihood of interaction-related adverse drug events, which are frequently preventable. Aim We aimed to identify, profile, and analyse potential antidepressant drug-drug interactions in information-seeking antidepressant users. Methods We retrospectively analysed antidepressant-related drug-drug interaction enquiries from patients or carers who contacted a pharmacist-led Australian national medicines call centre over an 8-year period to determine patient characteristics, concomitant drugs involved, prevalence and type of antidepressant-related drug-drug interaction across life stages, and associated risks. Results Of 3899 antidepressant drug-drug interaction calls, the most frequent concomitant drugs were antipsychotics, opioids, benzodiazepines, and complementary medicines. Narrative analyses of 2011 calls identified 81.0% of patients with potential drug-drug interactions and 10.4% categorised with worrying symptoms. The most frequent drug-drug interaction risks were excessive sedation, increased anticholinergic effects, serotonin syndrome, and suicidal thoughts. Carers of children aged <15 years and older adults (65-74 years) were more likely to report experiencing worrying symptoms. Although more potential pharmacodynamic than pharmacokinetic interactions were recorded, pharmacokinetic interactions tended to have more significant clinical impact. Discussion Antidepressant users often have information gaps and safety concerns regarding drug-drug interactions that motivate help-seeking behaviour. Symptoms and drug-drug interaction consequences may be underestimated in these patients. Primary care health professionals have a role in proactively addressing the risk of drug-drug interactions to support benefit-risk assessment and shared decision-making.